Evaluación de la planta Calacala de purificación de agua del municipio de Beltrán (2017)
This document presents the evaluation of the PPP of the municipality of Beltrán Based on the information available until August 2016. Chapter 2 summarizes the basic concepts of the process of purification of Water and chapter 3 the current legal framework for the control of drinking water. Chapters 4 and 5 present the background and components of the plant Of purification of the municipality of Beltrán, respectively. Chapter 6 presents the operating conditions of the PPA. Chapter 7 includes the characterization of the PPA affluent and effluent With treatment efficiencies. Finally, Chapter 8 draws the relevant conclusions